Teachers perception about their training process through the Eduticom model using Interactive Whiteboard. (25th May 2010) - Cortada, Meritxell; Badilla, M? Graciela Badilla; Riera, Jordi
With the incorporation of Information and Communication Technologies (ICT) in education, especially the Interactive Whiteboard (IWB), the need for a proper teacher training process emerges in order to adjust the integration and didactic use of this tool in the classroom. This paper discusses the teachers' perception on the training process for ICT integration. Its main aim is to contribute to the unification of minimum criteria for effective ICT implementation in any training process for active teachers. This case study begins from the development of a training model called Eduticom which was put into practice in four schools in Catalonia, Spain. Findings indicated different teachers' needs such as an appropriate infrastructure, a proper management and a flexible training model which essentially addresses methodological and didactic aspects of IWB use in the classroom.